2001
DOI: 10.1177/135910530100600606
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Iatrogenically Acquired Hepatitis C Infection on the Well-being and Relationships of a Group of Irish Women

Abstract: The views of 32 women with iatrogenic Hepatitis C on its impact on their sense of wellbeing were elicited through focus groups. The views obtained were analysed using 'interpretative phenomenological analysis'. Accounts of profound fatigue, reactive depression, and deterioration in cognitive functioning predominated. Work outside and inside the home was severely curtailed or stopped. Marital relationships were affected, sometimes adversely, as were relationships with children and other family members. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…Some of the included studies assessed the same group of people but reported on different aspects of living with HCV: Olsen et al [21], Olsen et al [22], and Olsen et al [23]; Harris [24] and Harris [25]; and Tompkins et al [60] and Wright et al [61]. Thirty-eight studies included participants from a general population [21, 23–59], seven included participants who were IDUs [22, 60–65], and one included participants who received contaminated blood products [66]. The broad themes identified did not differ across these populations, so the findings are described together.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the included studies assessed the same group of people but reported on different aspects of living with HCV: Olsen et al [21], Olsen et al [22], and Olsen et al [23]; Harris [24] and Harris [25]; and Tompkins et al [60] and Wright et al [61]. Thirty-eight studies included participants from a general population [21, 23–59], seven included participants who were IDUs [22, 60–65], and one included participants who received contaminated blood products [66]. The broad themes identified did not differ across these populations, so the findings are described together.…”
Section: Resultsmentioning
confidence: 99%
“…IPA was originally developed for analyzing semistructured interview data, but more recently has been applied to focus group data (e.g., Dunne & Quayle, 2001;Flowers, Duncan, & Frankis, 2000). The dilemmatic nature of decision-making about life-prolonging technologies was used as a conceptual framework from which to develop the interpretative analysis.…”
Section: Introdctionmentioning
confidence: 99%
“…Where IPA research using focus group data has been undertaken previously, its authors have tended to highlight the benefits of doing so while at the same time urging caution with this type of analysis (e.g., Dunne & Quale 2001;Flowers et al 2001;Green et al 2003). For example, Flowers et al (2001) noted that their focus on shared understandings led to a neglect of idiosyncratic experiences.…”
Section: Discussionmentioning
confidence: 94%
“…For example, MacLeod et al (2002) interviewed "family units" presenting at a consultation. More commonly, the familiar format of a "facilitated group discussion" has been employed (e.g., de Visser & Smith 2007;Dunne et al 2001;Flowers et al 2000;Flowers et al 2001). In each case, the standard IPA approach of bottomup analysis, grounded in accounts of experience, was employed.…”
Section: Ipa and Focus Groupsmentioning
confidence: 99%